The Relationship Between Self-Concept and Students' Mathematical Adaptive Reasoning Abilities - Rani Rahayu Sarah; Rostina Sundayana (Journal of Practice Learning and Educational Development, 2026)
This study aims to analyze the relationship between self-concept and adaptive mathematical reasoning ability of eighth-grade students at SMP Negeri 3 Tarogong Kidul, Garut. Adaptive reasoning ability is an important skill in facing the challenges of the 21st century, while self-concept is suspected as one of the internal factors that influence it. This study uses a quantitative approach with a non-experimental method. The research subjects were 30 students selected through a purposive sampling technique. The instruments used included a descriptive test to measure adaptive reasoning ability and a Likert scale questionnaire to assess self-concept. The normality test using Shapiro-Wilk showed that both variables were not normally distributed, so the relationship analysis was carried out using Spearman Rank correlation. The results showed a significant relationship between self-concept and students' adaptive mathematical reasoning ability, marked by a significance value of 0.000 <0.05 and a correlation coefficient of 0.624 which is included in the strong category. The coefficient of determination of 38.9% indicates that self-concept contributes to adaptive reasoning ability, while the remaining 61.1% is influenced by other factors, such as learning interest, conceptual understanding, and student creativity. Overall, this study concludes that mathematical self-concept plays an important role in improving students' adaptive reasoning ability, so strengthening the affective aspect needs to be part of the mathematics learning strategy